Trendy Veil: Law, Function, and Its Stigma on Muslim Society - Musda Asmara; Rahadian Kurniawan; Wahyu Abdul Jafar; Anggoro Sugeng; Sakirman Sakirman (JURIS (Jurnal Ilmiah Syariah), 2023)
The trendy Veil was a phenomenon among young women, especially after the Covid 19 outbreak. Many wear the veil as well as a mask to prevent disease. The purpose of this study was to reveal facts related to law, function, and social stigma against women who wear the trendy veil. This research was field research that used a normative approach. Data collection techniques in this study were interviews and documentation. At the same time, the analysis technique used in this study is descriptive. The findings in this study were that the law on wearing a trendy veil was sunnah as long as a trendy veil follows the general rules of dress for Muslim women. The trendy veil has three functions: worship, social, and health. In addition, there has been a change in the stigma of women who wear the veil today, especially women who wear trendy veils. The negative stigma against women who wear the veil has begun to disappear. The Muslim community has considered the trendy veil a necessity and a common thing.